Affidavit Sebagai Ratio Decidendi Putusan Onslag - Sinaga, Roulinta Yesvery (PATTIMURA Legal Journal, 2023)
Introduction: The court concluded that the defendant had committed the acts alleged but that these did not constitute a criminal offense and were properly classified as a civil matter (onslag van recht vervolging) under Article 191(2) of the Indonesian Criminal Procedure Code. This ruling provoked profound dissatisfaction among KSP Indosurya depositors, who felt that their rights had not been adequately addressed within the criminal justice framework. Central to the court's legal reasoning was the submission of an Affidavit—a sworn declaration treated as a pivotal piece of evidence. Purposes of the Research: This study seeks to examine the existence and significance of the Affidavit as a foundational basis for the court's onslag decision. Methods of the Research: Utilizing a normative legal methodology, this research combines a case approach and statutory analysis and is conducted through a descriptive-analytical framework. Results Originality of the Research: An Affidavit, or a sworn statement verified, becomes evidence in court proceedings. The emergence of the Affidavit is a manifestation of good intentions from KSP Indosurya, thus becoming the ratio decidendi in the judgment. The judge, in deciding the KSP Indosurya case, undoubtedly considers the legal objectives of justice, legal certainty, and utility. The basis for consideration, due to the presence of the Affidavit, has undoubtedly achieved legal certainty; however, the element of utility still needs to be questioned. The role of the judge in rendering a decision should not be solely based on the existence of evidence but should also involve a conscience that contributes partially. The role of conscience should enable it to penetrate the reasons why parties bring criminal claims, thereby producing a clear result. The judge's decision should serve as a deterrent for cooperatives' mafia or potential mafia due to their malicious intent.